2005
DOI: 10.1002/jms.752
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a liquid chromatographic/tandem mass spectrometric assay for the quantitation of nucleoside HIV reverse transcriptase inhibitors in biological matrices

Abstract: Besides liquid chromatographic (LC)/UV methods adapted to therapeutic drug monitoring, there is still a need for more powerful techniques that can be used for pharmacological research and clinical purposes. We developed an LC method coupled with tandem mass spectrometry (MS/MS) to separate, detect and quantify with high sensitivity the nucleoside analogues used in multitherapies (zidovudine, stavudine, zalcitabine, didanosine, lamivudine and abacavir) in plasma and in the intracellular medium. We worked on two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…The resulting solutions were filtered and analyzed using standard LC-MS/MS conditions (calibration range, 0.5 to 200 ng/ml). Intra-and interday precisions and accuracies tallied with previously reported recommendations (48) and previously reported values (15). No interlaboratory tests have been performed, since this kind of quality control exists only for protease inhibitors and nonnucleoside reverse transcriptase inhibitors (19,33) but not for NRTI.…”
Section: Lc-ms/ms Analysis Of Nrti-mp/tp and Dt-tpsupporting
confidence: 54%
See 1 more Smart Citation
“…The resulting solutions were filtered and analyzed using standard LC-MS/MS conditions (calibration range, 0.5 to 200 ng/ml). Intra-and interday precisions and accuracies tallied with previously reported recommendations (48) and previously reported values (15). No interlaboratory tests have been performed, since this kind of quality control exists only for protease inhibitors and nonnucleoside reverse transcriptase inhibitors (19,33) but not for NRTI.…”
Section: Lc-ms/ms Analysis Of Nrti-mp/tp and Dt-tpsupporting
confidence: 54%
“…Extraction and LC-MS/MS analysis of NRTI from plasma samples. The procedure for extraction and LC-MS/MS analysis of NRTI from plasma samples was an improved version of a previously reported assay (15), with minor modifications concerning the working volume of samples. Only 250 l of plasma was taken, spiked with 50 l of internal standard (2-chloroadenosine and zalcitabine), but the preparation process remained unchanged.…”
Section: Lc-ms/ms Analysis Of Nrti-mp/tp and Dt-tpmentioning
confidence: 99%
“…The boost given by the technological developments of novel mass analyzers [13], has produced several LC coupled with MS/MS methods [14][15][16]. Recently, Benech and co-workers [17][18][19][20][21] used LC-MS/ MS with selected reaction monitoring (SRM) to directly quantitate the intracellular triphosphorylated metabolites of anti-HIV nucleosides, alone or in combination, in human PBMCs of HIV-positive patients. As part of our on going program to develop new bioanalytical methods, our group has previously reported that CE coupled with ESI-MS/MS was an excellent technique for the separation and quantitation of various anti-HIV nucleosides [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, LC coupled with tandem mass spectrometry (MS/MS) was applied to measure zidovudine concentrations in plasma Volosov et al, 2002;Font et al, 1998;Compain et al, 2005Compain et al, , 2007King et al, 2006;Pereira et al, 2000). This technique combines the advantages of LC separation and the high sensitivity and specificity of MS/MS, but sometimes it is not sufficiently exploited with respect to the chromatographic step.…”
Section: Introductionmentioning
confidence: 99%